ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS MATERI SEGIEMPAT DITINJAU DARI KEMAMPUAN MATEMATIK SISWA - Yuliana Maria Sema; Lely Suryani; Maria Trisna Sero Wondo (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to determine the ability to think mathematically creatively in terms of the mathematical ability of grade VII students of SMPN SATAP Ligalejo in solving quadrilateral problems. This type of research uses the Qualitative Descriptive method. The selection of research subjects is based on the category of students' mathematical abilities, that is students with high, medium and low skills. So 6 students were obtained from 22 students. The instruments used are tests, interviews and documentation. The data collection techniques used are test, interview and documentation techniques. Meanwhile, the data analysis technique used is qualitative data analysis starting with data reduction, data display and drawing conclusions. This study's results showed that students with high mathematical abilities were included in the inter-achievement of mathematical creative thinking abilities quite well, with an average score of 52.46%.  Meanwhile, students who have moderate mathematical ability are included in the inter-achievement of mathematical creative thinking skills are not good, with an average score of 31.15%. Students who have low mathematical ability are included in the inter-achievement of mathematical creative thinking ability is very poor, with an average score percentage of 16.39%.